2016
DOI: 10.1016/j.cgh.2015.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Inflammatory Bowel Diseases Monitoring Index for Use With Mobile Health Technologies

Abstract: We developed and validated a scoring system to monitor disease activity in patients with CD and UC that can be used with mobile technologies. The indices identified clinical disease activity with area under the receiver operating characteristic curve values of 0.9 or higher in patients with CD or UC, and endoscopic activity in patients with UC but not CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 21 publications
(23 reference statements)
1
53
0
Order By: Relevance
“…However, decision support tools in IBD are now feasible as current eHealth technologies can provide the necessary components, including functionalities that allow recording of PRO and clinical biomarkers, validated disease severity indices on which algorithms can be based and a means of automatically delivering treatment suggestions in real time . Validated disease activity indices, such as the Crohn Disease Activity Index (CDAI) and the Simple Clinical Colitis Activity Index (SSCAI), can be reliably completed by patients using eHealth tools to measure disease activity . Moreover, home‐based measurement of faecal calprotectin is feasible and has been shown to agree with hospital‐based enzyme‐linked immunosorbent assays (ELISA) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, decision support tools in IBD are now feasible as current eHealth technologies can provide the necessary components, including functionalities that allow recording of PRO and clinical biomarkers, validated disease severity indices on which algorithms can be based and a means of automatically delivering treatment suggestions in real time . Validated disease activity indices, such as the Crohn Disease Activity Index (CDAI) and the Simple Clinical Colitis Activity Index (SSCAI), can be reliably completed by patients using eHealth tools to measure disease activity . Moreover, home‐based measurement of faecal calprotectin is feasible and has been shown to agree with hospital‐based enzyme‐linked immunosorbent assays (ELISA) …”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22] Validated disease activity indices, such as the Crohn Disease Activity Index (CDAI) and the Simple Clinical Colitis Activity Index (SSCAI), can be reliably completed by patients using eHealth tools to measure disease activity. [35][36][37] Moreover, home-based measurement of faecal calprotectin is feasible and has been shown to agree with hospital-based enzyme-linked immunosorbent assays (ELISA). 38,39 Previous eHealth decision support tools have lacked a multi-stage design process with appropriate consultation, which is necessary given the complex interactions between key stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…This quality makes patients with chronic gastrointestinal disorders the ideal candidates to target for improved self-managed or collaborative management strategies incorporating remote monitoring and consultation. 64 …”
Section: Convergence Of Smartphones Mobile Apps Sensors and Telemementioning
confidence: 99%
“…70 Continuous uncontrolled gathering and sharing of information via modern remote sensors, especially those that are embedded in clothes and environment, can compromise patients’ privacy. 64 Physicians on their side must ensure the security and safety of their smartphones and digital devices to be used as a medical tool. 71,72 On a similar note, confidentiality of the data needs to be maintained to prevent inappropriate use.…”
Section: Limitations and Challengesmentioning
confidence: 99%
“…Research has shown associations between patient symptoms (e.g., stool frequency and rectal bleeding) and clinically assessed improvement; patient self-monitoring of symptoms, potentially facilitated by remote monitoring technology, on a weekly/daily basis may be an appropriate avenue to assess treatment benefit in clinical trials [23]. Remote monitoring can reduce the number of visits necessary for patients currently in remission, freeing up valuable resources for clinicians to devote to patients experiencing acute symptoms [24].…”
Section: Discussionmentioning
confidence: 99%